Principles and Practice of Interventional Pulmonology - Ernst, Armin.; Herth, Felix JF. (Springer New York : Imprint: Springer, 2013)
Principles and Practice of Interventional Pulmonology provides a comprehensive text covering all aspects of Interventional Pulmonology. Providing both pathophysiologic background as well as illustrated and clear instruction on how procedures ought to be performed, this text will be of great value to interventional pulmonologists, thoracic surgeons, surgical oncologists, and interventional radiologists.